Relocation of small and medium industries (SMIs) manufacturing to non-metropolitan areas: a lesson from USA and Canada - Abdul Aziz Ab Latif (2000)
Small and Medium Industries (SMIs) manufacturing are important to any nation because they are the sources of new ideas, new form of competitive advantage, creat new jobs, create income, and other multiplier effects associated with them. The future economic health of any nation depends on the country's ability to achieve greater success through small and medium industries, The availability of raw materials and cheap labour are the major contributing factors toward the trend of relocation of SMIs from urban to rural areas. The other explanation of the decentralisation phenomenon is the is the product life cycle theory of industrial relocation. The choice of location by SMIs managers is based on expectation to fufil firm's goal, and how it fits together with firm's short and long-term objectives. There are six primary concerns for selection of rural industrial locations. Those concerns are labour cost, labour unionisation, proximity to supplier of resources, proximity to market, proximity to other firm's facilities, and quality of life in the area.